Venous thromboembolism in in-hospital cirrhotic patients: A systematic review - da Cruz Renó, Leonardo; Tustumi, Francisco; Waisberg, Daniel Reis; Rocha-Santos, Vinicius; Pinheiro, Rafael Soares; Macedo, Rubens Arantes; Nacif, Lucas Souto; Ducatti, Liliana; De Martino, Rodrigo Bronze; Trevisan, Alexandre Maximiliano; Carneiro-D’Albuquerque, Luiz; Andraus, Wellington (Frontiers in Medicine, 2022)
Introduction Patients with liver cirrhosis are at a higher risk of hospitalization. The present review aimed to assess the risk of thromboembolism and its burden on hospitalized cirrhotic patients. Materials and methods A systematic review (PROSPERO: CRD42021256869) was conducted in PubMed, Embase, Cochrane, Lilacs, and a manual search of references. It evaluated studies that compare cirrhotic patients with venous thromboembolism (VTE) with cirrhotic patients without VTE or studies that compare cirrhotic patients with non-cirrhotic patients. No restrictions were set for the date of publication or language. The last search was conducted in June 2021. Results After selection, 17 studies were included from an initial search of 5,323 articles. The chronic liver disease etiologies comprise viral, alcohol, autoimmune, NASH (non-alcoholic steatohepatitis), cryptogenic, hemochromatosis, cholestasis, and drug-related. The included studies were conflicted regarding the outcomes of VTE, pulmonary embolism, or bleeding. Patients with cirrhosis associated with VTE had prolonged length of hospital stay, and patients with cirrhosis were at higher risk of portal thrombosis. Conclusion In-hospital cirrhotic patients are a heterogeneous group of patients that may present both thrombosis and bleeding risk. Clinicians should take extra caution to apply both prophylactic and therapeutic anticoagulation strategies. Systematic review registration [https://www.crd.york.ac.uk/PROSPERO/], identifier [CRD42021256869].